Collaborative Communication as a Marketing Communication Strategy (Case Study of BLP Beauty X Kopi Tuku) - Tandaju, Christina; Fransisca, Caroline (Universitas Mercu Buana, 2024)
Business competition in Indonesia makes local brands increasingly innovate for brand existence, one of which is by collaborating. Brand collaboration is a marketing strategy for brands to survive and retain customers and to achieve common goals, namely increasing sales, brand awareness, brand image and others. The collaboration carried out between BLP Cosmetics Collaboration followed by Marketing 4.0, namely from traditional to digital, is one of the operations of this research looking at the 5A approach where currently marketing is carried out not only offline but followed by online marketing. Apart from that, this research also uses good reputation theory and will evaluate the collaborative communication that has been created. The purpose of this research is to determine the collaborative communication carried out by BLP Cosmetics and Kopi Tuku as a marketing strategy and this collaboration also requires trust between brands and the marketing they carry out. This research method uses descriptive qualitative and will carry out observations and interviews with Kopi Tuku Marketing Communication and the CMO and founder of BLP Beauty. The results of this research are that TUKU & BLP realize the vision of each brand by being good neighbours. BLPFam also enthusiastically accepts collaboration resulting in market expansion, engagement with customers, increased brand awareness, brand image, brand value, and also sales. The 5A approach, which includes attention, appeal, ask, act, and advocate, was effectively utilized both offline and online. It was observed that the communication between the two brands was transparent and collaborative, leading to a strong and trusting partnership.